THE EFFECTIVENESS OF BISOPROLOL AND METFORMIN IN ARTERIAL HYPERTENSION AND METABOLIC SYNDROME - Khusainova Munira Alisherovna; Khaydarov Sanjar Nizamitdinovich; Khaydarova Zarrina Erkinovna (Journals Park Publishing, 2024)
Goal. Evaluation of the effectiveness of treatment of arterial hypertension (AH) with manifestations of metabolic syndrome (MS) with beta-blocker bisoprolol and its combination with metformin.
Keywords: bisoprolol, metformin, arterial hypertension, metabolic syndrome.